Programming Microsoft Dynamics NAV 2009 : develop and maintain high performance NAV applications to meet changing business needs with improved agility and enhanced flexibility /: develop and maintain high performance NAV applications to meet changing business needs with improved agility and enhanced flexibility. (2009) - Unknown
No abstract available